Impacts of trelagliptin and remogliflozin alone and in combination with Alpha Lipoic Acid on cardiac function in streptozotocin-induced diabetes mellitus in rats: Effects of trelagliptin, remogliflozin, and ALA on cardiac function in DCM - Abdullah Ali, Mohammed; Naji Alhassani , Ansam; Kareem Hamad, Badraldin (Cellular and Molecular Biology, 2023)
This study investigated the effects of trelagliptin and remogliflozin, alone and in combination with alpha lipoic acid (ALA), on cardiac biomarkers in diabetic cardiomyopathy (DCM). We aimed to assess the management of glucotoxicity consequences in streptozotocin-induced diabetic rats by measuring serum levels of pharmacologically active endogenous ligands. Forty-eight male rats were divided into different treatment groups, including negative control, positive control, and four experimental groups. After inducing diabetes, the rats were treated for 28 days, and serum levels of biomarkers associated with oxidative stress (malondialdehyde and thioredoxin-interacting protein), inflammation (nuclear factor NF-kappa-B p105 and lipoprotein-associated phospholipase A2), and myopathy (neprilysin and high selective cardiac troponin T) were measured. Immunohistochemical analysis of heart cells was also performed. The results showed that inducing hyperglycemia increased serum glucose levels and biomarkers associated with DCM. However, all treatment groups exhibited a significant decrease in these biomarkers and an increase in insulin levels compared to the diabetic control group. The groups receiving combination therapy with ALA showed greater improvements in cardiac biomarkers compared to the individual treatments. The immunohistochemical analysis supported these findings by demonstrating a reduction in the percentage area of cathepsin B, a protein involved in DCM pathophysiology. In conclusion, supplementing the base treatments with ALA showed promise in enhancing cardiac biomarkers associated with DCM. The combination of trelagliptin, remogliflozin, and ALA may have additional clinical value in managing DCM by targeting oxidative stress, inflammation, and glucotoxicity. However, further research is needed to validate these findings and explore their potential clinical applications.